2005
DOI: 10.1160/th05-02-0140
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of cellular multimerin 1 receptors: in vitro evidence of binding mediated by αΙΙbβ3 and αvβ3

Abstract: Multimerin 1 (MMRN1) is a large, soluble, polymeric, factor V binding protein and member of the EMILIN protein family. In vivo, MMRN1 is found in platelets, megakaryocytes, endothelium and extracellular matrix fibers, but not in plasma. To address the mechanism of MMRN1 binding to activated platelets and endothelial cells, we investigated the identity of the major MMRN1 receptors on these cells using wild-type and RGE-forms of recombinant MMRN1. Ligand capture, cell adhesion, ELISA and flow cytometry analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…As for the ATB highly expressed groups (Supplementary Figure 2), 12 genes displayed an increased trend and were in agreement with the previous studies (Pacis et al, 2015) (Supplementary Table 4). Among which, ACSL4 and CLU were related with lipid metabolic process (Kuch et al, 2014; Park et al, 2014), and MMRN1 and POSTN were relevant to cell adhesion (Adam et al, 2005; Michaylira et al, 2010). These results suggested that the top-20 genes for each pattern might provide potential molecular targets for the prevention, diagnosis, and treatment of LTBI and ATB individuals.…”
Section: Resultsmentioning
confidence: 99%
“…As for the ATB highly expressed groups (Supplementary Figure 2), 12 genes displayed an increased trend and were in agreement with the previous studies (Pacis et al, 2015) (Supplementary Table 4). Among which, ACSL4 and CLU were related with lipid metabolic process (Kuch et al, 2014; Park et al, 2014), and MMRN1 and POSTN were relevant to cell adhesion (Adam et al, 2005; Michaylira et al, 2010). These results suggested that the top-20 genes for each pattern might provide potential molecular targets for the prevention, diagnosis, and treatment of LTBI and ATB individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Forming a variety of di-sulfide linked multimers, ranging from a trimeric complex to multimers of many megadaltons in size (14), it is conceivable that MMRN1 could play a dynamic role in the cytoarchitectural and adhesive changes that accompany platelet aggregation and clot formation. Together, MMRN1 may therefore serve as an extracellular matrix (ECM) or adhesive protein mediating cellular attachment through the binding of ECM proteins and integrin receptors (15, 16). …”
Section: Discussionmentioning
confidence: 99%
“…The family includes EMILIN1 (Colombatti et al, 1985; Bressan et al, 1993; Doliana et al, 1999), EMILIN2 (Doliana et al, 2001), Multimerin1 (MMRN1; Hayward et al, 1991, 1995), and Multimerin2 (MMRN2; Sanz-Moncasi et al, 1994; Christian et al, 2001). Apart from MMRN1 that is deposited in the ECM but for the most part is sequestered in megakaryocytes, endothelial cells (ECs), and platelets granules (Adam et al, 2005), the members of the EMILIN family are constituents of the ECM Under normal conditions the expression of each individual gene overlaps with those of some other members of the family; the only exception is apparently the central nervous system, where only EMILIN2 is detected outside blood vessels, at least at the mRNA level (Braghetta et al, 2004). Moreover, EMILIN2 is specifically and abundantly expressed in mouse cochlear basilar membrane (Amma et al, 2003).…”
Section: The Emilin/multimerin Family Of Proteinsmentioning
confidence: 99%
“…MMRN1 is a soluble S–S linked homopolymer stored in platelets, megakaryocytes, and ECs and deposited in ECM (Hayward, 1997; Adam et al, 2005). It supports the adhesion of platelets, neutrophils, and ECs via integrin αvβ3 and α IIb β3 (Adam et al, 2005).…”
Section: Gc1q-independent Functionsmentioning
confidence: 99%